Doctors should choose communication strategies based on the patient's attitude toward disease and healthcare workers: a study in Jiangsu, China - Zheng, Fangjing; Lin, Aicui (Frontiers in Health Services, 2025)
ObjectiveWe aimed to determine patients’ expectations regarding curing their disease and potential communication preferences with healthcare providers, by analyzing factors such as education level, age, type of medical visit, and residential region, so as to assist healthcare workers in managing communication more effectively.MethodsA sampling survey was conducted involving 1,155 patients across nine public tertiary hospitals in Jiangsu Province, China. The survey questionnaire results were verified and organized, after which chi-square tests and Z-tests were conducted to analyze the responses to each question across different groups.ResultsAmong the educated population, the proportion of patients who believe that diseases can definitely be cured tends to decrease as the level of educational increases. Similarly, this proportion also tends to decrease with an increase in economic development across different regions. The proportion of patients who believe that they should fulfill their obligations during the treatment process but lacked understanding of how to do so also exhibits a similar trend. Adults under the age of 50, as well as outpatient and emergency patients, are more willing to cooperate with medical treatment, but often lack knowledge about how to do so.ConclusionHealthcare workers should select communication strategy that are suitable for patients considering their age, education, type of medical visit, and residential region and provide appropriate cure expectations to prevent communication issues.